Cuerpos e identidades on line: construcción de identidades corporales en el chat - Ortiz, Luz Marilyn (Colombian Applied Linguistics Journal, 2013)
This article aims to analyze the process of identity construction in relation to the body in virtual space, in the context of Computer Mediated Communication (CMC), particularly in chat device users. In the first part addresses the issue of identity in the digital age, from a non-essentialist concept of identity. In the second part analyzes the “epistemological emergence” of the body in the field of cyberspace. The third part deals with the effects of CMC modes and strategies of identity construction for chatters body, understood as a virtual enunciation device in which the subject is contextualizes using multimodal languages.